Facial recognition attendance system - Lew, Tian Pei (2023)
Attendance had become an important element to record the presence of students in the class so that the students can follow up the learning process. However, it was a drawback for the traditional manual attendance system which used paper and pen to sign attendance. This is due to the reason that traditional attendance system has the potential for error as students may sign for absent friends and the data can be easily manipulated. Therefore, a more reliable and efficient attendance system is needed. Facial recognition technology can be used to address these issues, reducing errors, preventing fake attendance, and saving time. In this project, Haar Cascade algorithm is used in this system to recognize faces. A web-based system was developed to let admin and instructor to manage the class and class attendance while the Android-based system was developed to let students to check their attendance.